ANALISIS MODEL REKRUTMEN DAN SELEKSI PENDIDIK DALAM KITAB TA’ALIMUL MUTA’ALLIM SYAIKH AZ-ZARNUJI - Mizanul Hasanah; Andika Aprilianto (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2020)
The important part of management is the role of an educator in applying management functions in the hope of reducing such complex problems. Therefore, it is natural that the educator (teacher) is a major component of the management function. If the teacher is of good quality, then education will be good. And vice versa. Discussions about educators are widely discussed by Muslim and western leaders from various generations. One Muslim figure who is quite famous in talking about education is Shaykh Az-Zarnuji. In choosing an educator according to Az- Zarnuji refers to primary data sources namely, Ta'alimul Muta'allimul is in terms of choosing teachers, let choose who is more pious, more waro 'and older. The goal is to get the ideal teacher criteria so that the actualization of knowledge and responsibility for the mandate to reach the pleasure of Allah SWT. In addition, the contextualization of teacher and student relationships intended by Zarnuji is to place the position of a teacher as a respectable figure in front of his students.